Pendampingan dan Sosialisasi Pembuatan Lubang Biopori Untuk Resapan Air Limbah Desa Tunikamaseang - Ramli, Rachmat; Santi, Santi; Latif, Sarifudin Andi; Alim, Andi; Wijayanti, Lumastari Ajeng; Aripa, Lusyana (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Biopori absorption holes are useful for processing organic waste from households and can be applied in narrow urban residential areas. Organic waste is put into biopore absorption holes, where the fauna in the soil will then convert the organic waste into compost. The resulting compost can be taken and used as fertilizer for surrounding plants. So the benefits of biopore infiltration hole technology in general are to reduce puddles, increase groundwater reserves, reduce the volume of organic waste. This socialization and training activity on making biopore absorption holes was carried out in Tunikamaseang village with the aim of providing knowledge about the benefits of biopore absorption holes and providing knowledge on how to make biopore absorption holes. The implementation of Biopori Socialization is carried out using mentoring and socialization methods. Based on the results of assistance and outreach, biopore holes were made in Tunikamaseang village in several locations. It is hoped that the creation of biopores will be a solution to reduce organic waste which is usually burned.